External Fixation Devices Within the Magnetic Resonance Imaging Bore: A Safety and Radiologic Analysis. Issue 1 (January 2021) - Ryan, Scott; Moon, Andrew S.; Gordon, Matthew; Flacke, Sebastian; Soni, Shalin; Salzler, Matthew J.; Stelma, Sarah; Marcantonio, Andrew
Abstract : Objectives: To (1) report the thermal changes encountered at the pin/skin interface in a cadaver with a knee-spanning external fixator inside the magnetic resonance imaging (MRI) bore and (2) report on the quality of the MRI sequences collected. Methods: Three commonly used external fixation systems were placed on cadaveric lower extremities to simulate knee external fixation. Fiber optic thermal probes were placed at the pin/skin interface of a femoral and tibial pin. A control probe was embedded in the soft tissues of the thigh. Full knee MRI scans were performed using a 1.5-Tesla magnet. Real-time thermal data were collected. A clinically significant increase in temperature compared with the control was defined as 2°C. Two blinded radiologists evaluated the images for image quality and overall diagnostic utility using a standardized 5-point grading scale. Results: There were statistically significant differences in the temperature changes between the femoral/tibial pin sites and the control probe sites during each phase of the MRI scan. However, there was only one clinically significant difference in temperature change during a single sequence of one MRI scan of one of the external fixator devices. Overall image quality was graded as a 4 for each image set with 100% interobserver agreement (k = 1.0). Conclusions: Despite significant differences in temperature changes between the pin sites and controls over multiple MRI sequences in commonly used external fixator devices, the differences in temperature change are likely not clinically relevant. Overall image quality and interpretability of the images were excellent. Abstract : Supplemental Digital Content is Available in the Text.